ANALYSIS OF THE INTERNATIONALIZATION STRATEGY OF MSMES KENDANG DJEMBE BLITAR - Sulhan, Muhammad; Sudarmiatin, Sudarmiatin (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
In the current era of globalization, it provides opportunities for MSMEs to market their products not only domestically but also in international markets. MSMEs Kendang Djembe Biltar is one of the MSMEs that has sold its products abroad. The purpose of this article is to identify the opportunities, threats, strengths, and weaknesses of the Kendang Djembe Blitar MSMEs to develop a suitable business strategy to increase the internationalization of the Kendang Djembe Blitar MSMEs. The approach used in this study is a SWOT analysis, the results of which are summarized in the External Factors Analysis Summary (EFAS) and Internal Factors Analysis Summary (IFAS) tables, then transfer the EFAS and IFAS values into a SWOT matrix to determine the business position as the basis for designing a suitable business strategy. to increase internationalization. The results of this study indicate that MSMEs Kendang Djembe Blitar are in quadrant I in the SWOT matrix, so the strategy that can be done in increasing its internationalization is to carry out a market development strategy, by expanding its marketing both take away and online media (digital marketing), developing business and multiplying destination countries for exporting their products, as well as adding a variety of products.